Module Development and Learning KIT Science Workshop for Madrasah Aliyah (MA) and Madrasah Tsanawiyah (MTs) Alif Laam Miim Surabaya Teachers - Munzil, Munzil; Ahmad Taufiq; Arif Hidayat; Hadi Suwono; Ida Rohmah Susiani; Nur Millaty Abadiah; Lya Rizka Herawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The problems faced by MA and MTs Alif Laam Miim in facing the merdeka curriculum are teachers' lack of understanding regarding the implementation of the merdeka curriculum, minimal training that teachers have participated in directly in creating teaching modules, and not having an ideal science learning KIT. This makes learning activities run less effectively. The solution offered by UM service team is to hold a workshop on developing learning modules and KITs for teachers at MA and MTs Alif Laam Miim, especially in science subjects (Physics, Chemistry, and Biology). The results of this workshop show an increase in teachers' understanding of how to develop modules and also the availability of learning KITs that are following the merdeka curriculum.